Fiscal pressure in cooperatives: a study by company size, regions and industries for the period 2008-2011 - Martínez Vargas, Julián; Carmona Ibáñez, Pedro; Pozuelo Campillo, José (REVESCO. Revista de Estudios Cooperativos, 2015)
Cooperatives consist of companies with special characteristics both in their regulation and in their taxation, traditionally most advantageous, that have important social functions. In this paper we obtain the corporate tax paid in order to measure the tax burden of cooperative enterprises and thus determine whether there are statistically significant differences by company size, regions and industries for the period 2008-2011. To this end we have used the new mandatory fiscal additional information disclosed in the annual financial statement from 2008, after the adaptation of business regulation to the international financial reporting standards in Spain.